Recruitment and Retention of International Graduate Students in US Universities - Srivastava, Soumya K.; Srivastava, Anurag K.; Minerick, Adrienne R.; Schulz, Noel N. (My University, 2010)
International students account for 3.5% of graduate students in the US with 17% enrolled in engineering programs in 2008. Recruiting and retention of International Graduate Students (IGS) is an essential and important consideration for US universities with increased competition from other countries. Understanding concerns and preferences influencing the IGS’s decision to choose a school in addition to factors affecting decisions to continue advanced degrees at a university will help schools effectively recruit and retain better quality students and thus increase research productivity. This paper addresses the design of comprehensive online survey to find preferences and influential factors affecting the decision of IGS in choosing a graduate school. IGS and alumni at US schools were invited anonymously to participate and complete the survey. Survey results were analyzed and interpreted both quantitatively and qualitatively. Results indicate that preferences of IGS to choose a school depend on their nationality, gender, age and several other factors. The paper concludes with recommendations to improve recruitment and retention, considering preferences and concerns of different groups of IGS and strategizing the efforts in view of diversity of IGS.
Keywords: International graduate students; Recruitment; Retention; Online survey